Beyond BRCA: New hereditary breast cancer susceptibility genes. Issue 1 (January 2015) - Economopoulou, P.; Dimitriadis, G.; Psyrri, A.
Highlights Sequencing of specific genes can identify families at risk of breast cancer. Multigene panel testing should be performed after consultation with a cancer geneticist. There is no consensus on when to use expanded models of testing. High penetrant breast cancer genes include TP53, PTEN, SKT-11, CDH1 and PALB2.